PENERAPAN METODE EKSPERIMEN DENGAN MEDIA REALIA DALAM PENINGKATAN PEMBELAJARAN IPA BAGI SISWA KELAS IV SEKOLAH DASAR - rahmawati, yuni (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Abstract: Application of Experiment Method with Realia Media in Increase of Science Learning for Elementary School Fourth Grade Student. The purposes of the research are: (1) describe the steps of experiment method with realia media to increase science learning process for elementary school fourth grade student, (2) to know the increase of science learning output with application of experiment method with realia media for elementary school fourth grade student, (3) identify obstacles and solutions in the application of experiment method with realia media in science learning for elementary school fourth grade student. This study is a Collaborative Classroom Action Research that was held in three cycle. Each cycle consist of planning, implementation, observation, and reflection. The results show that the application steps of experiment method with realia media can increase science learning of elementary school fourth grade students. In learning process the first cycle, student percentage reached 61,11%, in the second cycle 73,33%, and the third cycle increase to 85,53%. In the pre-action completeness percentage still 0% of all students, having performed the action in the first cycle of students completeness percentage increase to 47,73%, in the second cycle increase to 73,46% and the third cycle increase to 83,33%. Keywords: experiment method, realia media, science learning Abstrak: Penerapan Metode Ekperimen dengan Media Realia dalam Peningkatan Pembelajaran IPA bagi Siswa Kelas IV Sekolah Dasar. Tujuan penelitian ini adalah: ((1) mendeskripsikan langkah-langkah penerapan metode eksperimen dengan media realia yang dapat meningkatkan proses pembelajaran IPA bagi siswa kelas IV SD, (2) mengetahui peningkatan hasil belajar IPA melalui penerapan metode eksperimen dengan media realia pada siswa kelas IV SD, (3) mengidentifikasi kendala dan solusi pada penerapan metode eksperimen dengan media realia pada pembelajaran IPA bagi siswa kelas IV SD. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif yang dilaksanakan dalam tiga siklus. Tiap siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Hasilnya menunjukkan bahwa penerapan langkah-langkah pembelajaran metode eksperimen dengan media realia dapat meningkatkan pembelajaran belajar IPA bagi siswa kelas IV. Pada proses pembelajaran siklus I, persentase siswa mencapai 61,11%, pada siklus II 73,46%, dan pada siklus III meningkat menjadi 83,33%. Pada pra tindakan persentase ketuntasan siswa masih 0%, setelah dilaksanakan tindakan pada siklus I persentase ketuntasan siswa menjadi 47,73%, pada siklus II meningkat menjadi 73,46% dan siklus III meningkat menjadi 83,33%.   Kata Kunci: metode eksperimen, media realia, pembelajaran IPA